2007
DOI: 10.1073/pnas.0604353104
|View full text |Cite
|
Sign up to set email alerts
|

Mapping protein collapse with single-molecule fluorescence and kinetic synchrotron radiation circular dichroism spectroscopy

Abstract: We have used the combination of single-molecule Fö rster resonance energy transfer and kinetic synchrotron radiation circular dichroism experiments to probe the conformational ensemble of the collapsed unfolded state of the small cold shock protein CspTm under near-native conditions. This regime is physiologically most relevant but difficult to access experimentally, because the equilibrium signal in ensemble experiments is dominated by folded molecules. Here, we avoid this problem in two ways. One is the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
340
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(369 citation statements)
references
References 63 publications
27
340
1
1
Order By: Relevance
“…The reconfiguration time of Csp in the unfolded state in our simulations is on the order of 10 4 time units ($100 ns, which is comparable with experimental value, 20,59 50 ns). The work by Schuler and coworkers 21 suggested that around 20% of the b strands are formed after 1.3 ms dead time. This finding may be owing to the contribution of partially folded b1-b2-b3 strand and may be influenced by a contribution from a small fraction of the folded state.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reconfiguration time of Csp in the unfolded state in our simulations is on the order of 10 4 time units ($100 ns, which is comparable with experimental value, 20,59 50 ns). The work by Schuler and coworkers 21 suggested that around 20% of the b strands are formed after 1.3 ms dead time. This finding may be owing to the contribution of partially folded b1-b2-b3 strand and may be influenced by a contribution from a small fraction of the folded state.…”
Section: Resultsmentioning
confidence: 99%
“…With the advances in single-molecule techniques, valuable insights have been gained from recent single molecule fluorescence energy transfer (FRET) studies of the Csp from T. maritima. [17][18][19][20][21] The two-state folding dynamics has been demonstrated clearly at the single-molecule level. 17 In many experimental studies, 3,4,12 the fluorescence of a single tryptophan is used alone to probe the folding dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However it is not yet able to determine dissociation constants for proteins, measure the conformation and stability of proteins, or detect and quantify the interaction of a protein with small drug-like molecules or ligands. Greater sensitivity at the single molecule level has been achieved recently for the measurement of conformational changes by fluorescence correlation spectroscopy, though this again relies upon the labeling of proteins with a strong fluorophore such as Alexa or AttoOxa11 dyes, 24,25 or the use of highly fluorescent proteins such as yellow fluorescent protein (YFP). 26 Here we present a microfluidic measurement technique that enables the thermodynamic stability of reversibly unfolding proteins, and the affinity of a small molecule drug compound for a target protein, to be determined using small samples and with high precision.…”
Section: Introductionmentioning
confidence: 99%